Happy baby ABC - Holmes, Denise (London Priddy Books, 2023)
This book is focussed on different types of play, from toys to playing outside and doing arts and crafts together. The soft retro illustrations include sweet vignettes of babies and labelled images of what is in the scene to encourage early speaking skills, word-picture recognition as well as introducing babies to the world around them(3Rs
Linguistic notions
Keywords: Vocabulary